Research on the trusted environment of container cloud based on the TPCM - Guojie LIU; Jianbiao ZHANG; Ping YANG; Zheng LI (网络与信息安全学报)
Container technology is a lightweight operating system virtualization technology that is widely used in cloud computing environments and is a research hotspot in the field of cloud computing.The security of container technology has attracted much attention.A method for constructing a trusted environment of container cloud using active immune trusted computing was proposed, and its security meet the requirements of network security level protection standards.First, container cloud servers were measured through the TPCM and a trust chain from the TPCM to the container's operating environment was established.Then, by adding the trusted measurement agent of the container to the TSB, the trusted measurement and trusted remote attestation of the running process of the container were realized.Finally, an experimental prototype based on Docker and Kubernetes and conduct experiments were built.The experimental results show that the proposed method can ensure the credibility of the boot process of the cloud server and the running process of the container and meet the requirements of the network security level protection standard evaluation.